The Oxford handbook of American Islam - Smith, Jane I.; Haddad, Yvonne Yazbeck (Oxford University Press, 2015)
In this volume 30 of the field's top scholars examine historical and contemporary aspects of American Islam, and explore the meaning of religious identity in the context of race, ethnicity, gender, and politics.